(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
A new species of terrestrial orchid Habenaria nicobarica Murugan, Alappatt, Prabhu & Arisdason sp. nov. is described from South Nicobar Islands. Key to species of Habenaria in Andaman and Nicobar Islands, illustration and photograph of the new species are also provided. DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19271 Bangladesh J. Plant Taxon. 21(1): 77-81, 2014 (June)